Legal Politics the Position of Witnesses and the Right to Assitance by Advocates in Criminal Cases - RR Duni Nurbayanti; Agus Surono; Arti Panday (CV. Era Digital Nusantara, 2025)
The examination of witnesses is very important in the examination of criminal cases, because these witnesses can shed light on a case. A witness is an individual who has direct information about a criminal event. A person is brought forward as a witness because he immediately